Mathematical Mathematical Problem Solving Ability Of Vocational School Students On Problem Based Learning Model Nuanced Ethnomatematics Reviewed From Adversity Quotient - Sunandar, Muhamad Aris; Zaenuri, Zaenuri; Dwidayati, N.K. (Unnes Journal of Mathematics Education Research, 2018)
This study aims to analyze the students’ learning quality on the application of Problem Based Learning (PBL) Model nuanced ethnomathematics to students’ problem-solving abilities, and the patterns of problem-solving abilities of mathematics on the application of PBL nuanced ethnomathematics reviewed from Adversity Quotient (AQ) students. This is a mixed method research using a concurrent embedded design. Subjects in this study were determined based on AQ analysis using Adversity Response Profile (ARP) on tenth grade of pharmacy students of Vocational School of Muhammadiyah 3 Weleri, Kendal. Data collection techniques used in this research are observations, tests, and interviews. The results showed that learning with PBL model nuanced ethnomathematics gave impact on the quality to students’ problem-solving ability. The problem-solving ability of quitter students in solving problems is only up to the stage of understanding the problem. The NCTM indicator that can be achieved by quitter students is only the first indicator. Meanwhile the problem-solving ability of camper and climber students in solving the problem up to the re-checking stage. Camper and climber students can reach all NCTM solving indicators.